Transformasi Media Sosial sebagai Instrumen Pemasaran UMKM di Destinasi Ikonik Surabaya - Zainal Abidin Achmad; Fla Neysa Rahma Putri (Universitas Merdeka Malang, 2025)
Social media has become a strategic tool for MSMEs to expand their reach, increase brand awareness, and strengthen consumer interactions. Optimizing Instagram, TikTok, and Facebook enables MSMEs to attract buyers, foster loyalty, and refine strategies based on consumer feedback. Jalan Tunjungan in Surabaya serves as an iconic public space that combines historical value with modern tourist destinations and showcases MSME products. This study examines the utilization of social media as a marketing tool for MSMEs in the area, employing a qualitative case study method that incorporates observation, interviews, and content analysis. The results show that social media increases MSME visibility, expands the market, and strengthens Jalan Tunjungan's image as a center of the creative economy. Visual content based on the uniqueness of public spaces is more effective in attracting digital audiences. This study emphasizes the importance of synergizing public spaces and digital marketing to support MSME-based tourism and city identity.